2021
DOI: 10.1111/ene.15157
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar pathology and disability worsening in relapsing‐remitting multiple sclerosis: A retrospective analysis from the CombiRx trial

Abstract: Background and purpose Cerebellar damage is a valuable predictor of disability, particularly in progressive multiple sclerosis. It is not clear if it could be an equally useful predictor of motor disability worsening in the relapsing‐remitting phenotype. Aim We aimed to determine whether cerebellar damage is an equally useful predictor of motor disability worsening in the relapsing‐remitting phenotype. Methods Cerebellar lesion loads and volumes were estimated using baseline magnetic resonance imaging from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Given that the cerebellum is recently linked as a driver of disability in early and progressive MS, an easy walking test sensitive to cerebellar pathology could be of significant predictive benefit. 20,21 Indicators of gait coordination in PwMS have been previously associated only with cerebellar volume and no correlations with other brain structures were found. 22 Moreover, a recent study showed that physical disability can be explained by gray matter atrophy of the cerebellum lobules I-IV and the vermis.…”
Section: Discussionmentioning
confidence: 96%
“…Given that the cerebellum is recently linked as a driver of disability in early and progressive MS, an easy walking test sensitive to cerebellar pathology could be of significant predictive benefit. 20,21 Indicators of gait coordination in PwMS have been previously associated only with cerebellar volume and no correlations with other brain structures were found. 22 Moreover, a recent study showed that physical disability can be explained by gray matter atrophy of the cerebellum lobules I-IV and the vermis.…”
Section: Discussionmentioning
confidence: 96%
“…In white matter (WM), EDSS score was significantly correlated with WM lesion volume, central atrophy, lesion probability in the periventricular WM at the left frontal horn and around the posterior horns and with whole-brain volume particularly with widths of third and lateral ventricle [32,37,[43][44][45]. The presence of confluent lesions (in RRMS), higher number of T2 lesions, lower baseline T2-lesion volume (T2LV), lower normalized brain volume (NBV), higher percentage brain volume change (PBVC) between year 2 and baseline and presence of � 4 slowly expanding lesions (SELs) were defined as prognostic factors for EDSS worsening and disability progression [46][47][48]83].…”
Section: Mri Markers Predicting the Disability Progressionmentioning
confidence: 99%